Hubungan Pengetahuan Perawat Tentang Keselamatan Pasien dengan Penerapan Sasaran Keselamatan Pasien di Rumah Sakit Demak - Idiasari, Intan; Purnomo, Muhammad; Kartikasari, Fitriana (Innovative: Journal Of Social Science Research, 2025)
Patient safety is a systematic effort to protect patients from injury due to medical errors, and nurses play an important role in implementing the six patient safety goals (PSGs). In Demak Hospital, patient safety incidents are still a concern, so efforts are needed to improve nurses' knowledge and compliance with PSGs. This study aims to analyze the relationship between nurses' knowledge of patient safety and the implementation of PSGs in inpatient rooms. Using a quantitative method with a cross-sectional correlational design on 101 nurses, data were collected through a questionnaire on knowledge and implementation of PSGs, then analyzed using the Spearman Rank test. The results showed that most nurses had good knowledge (72.3%) and had implemented PSGs (97.1%). There was a significant relationship between the level of nurses' knowledge and the implementation of PSGs with a p value of 0.004 and a correlation coefficient of 0.283. These findings emphasize the importance of increasing education and regular training for nurses to strengthen the implementation of PSGs and create a safer hospital service environment for patients.